2021
DOI: 10.5144/0256-4947.2021.171
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss among patients with type 2 diabetes mellitus: a cross-sectional study

Abstract: BACKGROUND: Hearing loss is an underestimated comorbid condition in type 2 diabetes. OBJECTIVES: Investigate hearing loss as a comorbidity associated with type 2 diabetes mellitus and evaluate the factors associated with hearing loss. DESIGN: Cross-sectional. SETTING: Tertiary care center, diabetes clinic. PATIENTS AND METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 16 publications
6
14
1
Order By: Relevance
“…In the current study, the overall magnitude of SNHI among the participants was 50.49% (95% CI; 45.69%, 55.26%). It was consistent with studies conducted in Australia 50%, 22 Pakistan 46.1%, 23 Switzerland 46.9%, 11 Taiwan 47%, 24 Saudi Arabia 49%, 25 South Africa 55%, 26 and Egypt 51.3%. 27 The consistency in study design and participant characteristics may account for the observed trend.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, the overall magnitude of SNHI among the participants was 50.49% (95% CI; 45.69%, 55.26%). It was consistent with studies conducted in Australia 50%, 22 Pakistan 46.1%, 23 Switzerland 46.9%, 11 Taiwan 47%, 24 Saudi Arabia 49%, 25 South Africa 55%, 26 and Egypt 51.3%. 27 The consistency in study design and participant characteristics may account for the observed trend.…”
Section: Discussionsupporting
confidence: 91%
“…We found that 74.7% of diabetic patients were experiencing some level of HL. This figure closely mirrors but is greater than 66.2%, as documented by Al-Rubeaan et al 19. Moreover, it is also greater than the values identified by Bamanie and Al-Noury in Saudi Arabia, Mozaffari et al in Iran, Uchida et al in Japan and Cheng et al in the USA which reported percentages of 52.3%, 30.0%, 39.1% and 46.0%, respectively 20–23.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, the duration of diabetes does not describe the progression of diabetes. Despite their involvement in diabetic complications like neuropathy,17 19 47 these factors might impact SNHL differently across various populations, necessitating further investigation. A 2018 meta-analysis revealed an escalating HL trend with prolonged diabetes duration,47 while another study48 noted a J-shaped link between HbA1c and high-frequency hearing impairment among baseline participants with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…37 In the present study, the prevalence of hearing impairment among the studied group was 12.6% and deafness was 1.4%. This is lower than that observed in a Saudi study by Al Rubeaan et al 38 among patients with type 2 DM where 49% of patients had hearing loss in both ears, 8.3% in the right ear only, 8.9% in the left ear only, and 29% had disabling hearing loss.…”
Section: (contrasting
confidence: 64%